Réponses

2013-12-18T21:28:32+01:00
A)
5 - 2(3x + 4)= 4x + 6
5 - 2(3x + 4) - 4x - 6 = 0
5 - 6x - 8 - 4x - 6 =0
5 - 10x - 14 = 0
(- 9) - 10x = 0
-10x = 9
x = -(9/10) = -0,9

b)
2 - (3 - 4x) = 2(3 - 4x)
2 - 3 + 4x = 6 - 8x
2 - 3 + 4x - 6 + 8x = 0
(-1) + 12x - 6 = 0
(-7) - 12x = 0
-12x = 7
x = -(7/12) 

c)
7(2x - 5) - 3x = 4 + (8x + 1)
14x - 35 - 3x = 4 + 8x + 1
11x - 35 = 3 + 8x
11x - 35 - 3 - 8x = 0
3x - 38 = 0
3x = 38
x = 38/3

Voilà :)
tes résulta son faux car les équation ne son pas équilibrer regarde l'équation avant de te lancer dans des calcules